Karakteristik Kelompok Pendukung ASI dengan Kelancaran ASI - Farida Yuliani (Fakultas Ilmu Kesehatan Universitas Setia Budi Surakarta, 2019)
Giving ASI is the basic capital of forming a quality human being where this process starts at an early age, especially if the mother gives her ASI exclusively. Exclusive breastfeeding is carried out from birth to a 6 month old baby without other food or drinks. The coverage of exclusive 6 months breastfeeding in Indonesia is still far from the world average of 38%. This study aims to determine the characteristics of KP-ASI with the smooth operation of breast milk in Gayaman Village, Mojoanyar District. This study uses analytical survey methods with a correlational research design. Data collection method with cross sectional approach. The population in the study were breastfeeding mothers who had babies 0-6 months as many as 25 people. The results showed that from several characteristics there were 3 characteristics that influence the smoothness of breastfeeding, namely the characteristics of the number of children, education and sources of information, where each characteristic had a value of p value <0.05. While the characteristics of age and work are not related to the smooth operation of breast milk. Counseling from health workers needs to be improved in nursing mothers since pregnancy, especially in the third trimester. Support from the family and the environment is also needed so that nursing mothers feel calm, comfortable during the nursing process.